Effectiveness of using Conceptualized Acqusition with Open Ended Quessisted Model to Improve Student's Critical Thinking Ability - Ellis Mardiana Panggabean (Eduvest - Journal of Universal Studies, 2022)
In learning activities that are oriented to the needs and abilities of students, it is necessary to provide a variety of learning situations that are adequate for the material which is presented and this should be tailored to the abilities and characteristics of students. This study aims to describe the effectiveness of conceptualized acquisition with open ended question-assisted model in improving critical thinking ability of students. The research design is the control group of pre-test post-test to the students of mathematics education program at Muhammadiyah University in North Sumatra. Based on the results of data analysis, it is found that the critical thinking ability of students who are taught with Conceptualized Acquisition with Open Ended Question-Assisted Model is better than the critical thinking ability of students who are taught with conventional learning model on lectures of Algebra Structure II and Conceptualized Acquisition with Open Ended Question-Assisted Model are effective in improving the critical thinking ability of students in the lecture of Algebra Structure II.